ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PELAPORAN PERUSAHAAN MELALUI INTERET (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2013) - Ega Dastentya Oktavia; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2015)
This study aimed to analyze the factors that affect the reporting of the company via the Internet on companies listed in Indonesia Stock Exchange in 2013. The company which increase voluntary information disclosure on the company's website can reduce information asymmetry. The information disclosed by the company is a signal which indicates that the company is better than other companies. Such disclosure is made to create transparency in the company and increase public confidence. The results showed that the status of the listing companies in the Corporate Governance Index, types of non-financial industries and the size of the company may increase voluntary information disclosure in the company's web site significantly, while the profitability does not affect the level of voluntary disclosure in the company's web site.